The Implementation of Canva Application to Enhance Students' Creativity in Graphic Design at SMPIT Tenggarong Seberang - Laili Azkia; Meylika Efrianti; Maulisa; Siti Sumiatun; Mamnuatus Sakina; Amin Nasrullah (JOSAR (Journal of Students Academic Research), 2025)
This study examines the effectiveness of the Canva application as an instructional tool to enhance creativity among seventh-grade students in graphic design at SMP IT Tenggarong Seberang. Employing a Classroom Action Research (CAR) methodology, the research was conducted over two cycles involving 44 students. The first cycle revealed that the integration of Canva did not significantly improve student engagement or creativity, with an average participation rate of 56% and an average score of 67.95. Consequently, modifications were made for the second cycle, focusing on clearer instruction and increased student interaction. The results of the second cycle demonstrated substantial improvements, achieving an 84% participation rate and an average score of 83.4, indicating that most students met the mastery criteria. Observations showed enhanced creativity in students’ graphic design projects, highlighting the positive impact of using technology in the classroom. This study underscores the potential of Canva as a versatile educational tool that fosters creativity and engagement, making it beneficial for modern educational practices. Future research may investigate the long-term effects of such applications on student learning outcomes across various subjects and educational levels.